Experimental behaviour and failure of beam-column joints with plain bars, low-strength concrete and different anchorage details - Coşgun, Cumhur; Türk, Ahmet Murat; Mangır, Atakan; Coşgun, Turgay; Kıymaz, Güven (Pergamon-Elsevier Science Ltd, 2020)
In framed structures, both steel and reinforced concrete, beam-column joints play a very crucial role in terms of seismic resistance. Under the effects of high lateral seismic loads, beam-column joints are subjected to high forces and moments and their behaviour have a significant influence on the response of the structure. Poor seismic performance of inadequately detailed joints can lead to the total or partial collapse of reinforced concrete frame structures. The use of low strength concrete, plain reinforcing bars, problematic anchorage details and inadequate transverse reinforcement in beam-column joints are the factors increasing the failure risk of the structures during severe earthquakes. In this paper, an experimental study on the cyclic behaviour of reinforced concrete exterior beam-column joints is presented. The study aims at investigating the effects of the longitudinal beam reinforcement anchorage detail on the joint performance and quantifying the level of contribution of retrofitting the joints by fiber reinforced polymer sheets (FRP). Three different details were considered in the test program including the longitudinal reinforcement of the beam being anchored within the joint with 90-degree hooks, 180-degree hooks and straight bar (no hook). All of the test specimens were produced using low strength concrete and plain bars to represent the conditions of joints of existing deficient reinforced concrete building structures. In the first series of tests, four 2/3 scale reinforced concrete beam-column joint specimens were tested by adopting a displacement controlled and quasi-static load application method to assess the performance of joints with the above-mentioned anchorage details. The load was applied in a reversed cyclic fashion. The second series of tests were carried out on two additional specimens with the same details as described above but strengthened using FRP sheets. The response of the specimens were evaluated and compared in terms of load-drift, displacement hysteretic behaviour. It was found out that the problematic anchorage details have a very significant adverse effect on the seismic performance of the joints. On the other hand, FRP retrofitting has resulted in a significant increase in peak loads and sustained ductility particularly for the specimens for which reinforcement slippage was not a governing mode of failure.
Keywords: Reinforced Concrete; Beam-Column Joint; Anchorage Detail; FRP Retrofit; Low-Strength Concrete